2014
DOI: 10.1063/1.4896103
|View full text |Cite
|
Sign up to set email alerts
|

The influence of random indium alloy fluctuations in indium gallium nitride quantum wells on the device behavior

Abstract: Articles you may be interested inInGaN/GaN multiple-quantum-well light-emitting diodes with a grading InN composition suppressing the Auger recombination Appl. Phys. Lett. 105, 033506 (2014); 10.1063/1.4891334 High efficiency InGaN/GaN light emitting diodes with asymmetric triangular multiple quantum wells Appl. Phys. Lett. 104, 091111 (2014); 10.1063/1.4867023Effect of V-defects on the performance deterioration of InGaN/GaN multiple-quantum-well light-emitting diodes with varying barrier layer thicknessIn thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 42 publications
4
110
0
Order By: Relevance
“…The strong variations in the hole ground state energies in cplane systems are attributed to hole wave function localization effects due to random alloy fluctuations [28,29,35]. To confirm this behavior in a nonpolar system, Fig.…”
Section: Gs and Holementioning
confidence: 99%
See 1 more Smart Citation
“…The strong variations in the hole ground state energies in cplane systems are attributed to hole wave function localization effects due to random alloy fluctuations [28,29,35]. To confirm this behavior in a nonpolar system, Fig.…”
Section: Gs and Holementioning
confidence: 99%
“…Obviously, these approaches completely neglect wave function localization arising from effects that could be attributed to the microscopic alloy structure. Recently, continuum-based approaches have been modified to include random alloy fluctuations [27][28][29]. Even though such an approach captures some of the localization effects introduced by alloy fluctuations it cannot reveal the microscopic origin of localization effects, including in particular the presence of In-N-In-N chains as shown by density functional theory (DFT) [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Regarding with our recent studies, the indium fluctuation incorporated into the simulation model is exceptionally fitting the experimental L-I-V curves by adopting more reasonable material parameters. 10,11 On the other hand, many researches have been reported that the inverted hexagonal V-shaped pit (V-pit) formation are considered to be induced by TDs, 12,13 where V-pits might be the key role to improve the device efficiency under such high dislocation densities. 14 The studies show that active regions in structures with the V-pit are composed of the normal lateral c-plane quantum wells (QWs) and inclined sidewall [1011] facet QWs, where the indium composition of lateral c-plane QWs is higher than that of inclined QWs.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13]), which cannot genuinely account for hot carriers and generally also produces larger turnon voltages for MQW LEDs than observed experimentally. [14] Many reasons have been suggested to explain this discrepancy, including charge transport through indium fluctuations, [15] V-shaped pits, [16] tunneling through traps [17] or hot carrier transport. [18] At present it is, however, unclear if the discrepancy is of a physical origin or if it arises simply because the very foundations of the widely adopted DD model make it incapable of predicting the most essential device-level characteristics of LEDs.…”
Section: Doi: 101002/aelm201600494mentioning
confidence: 99%